The Effect of Cutting Parameters on Surface Roughness When Milling Bio Ceramic - Andi amirul; Noor Hakim Rafai (Research Progress in Mechanical and Manufacturing Engineering, 2024)
This study investigates the mechanical properties of bio-ceramics, especially hydroxyapatite (HAP) as well as the effect of milling parameters on surface roughness quality, using the method known as Taguchi being utilised for optimisation. Dry mixing, compression, and sintering at 1200°C were employed to prepare HAP samples mixed with 1% Polyvinyl Alcohol (PVA) and 4% Polyethylene Glycol (PEG) binders. SEM, XRD, modulus of rupture, density, porosity assessments, Vickers hardness, and surface roughness test were just a few of the comprehensive tests that were conducted out to evaluate the mechanical properties and identify the materials. The Taguchi approach was utilised all over the machining process on a CNC milling machine in order to determine the best combination of cutting speed, feed rate, and depth of cut for the best possible surface smoothness. The findings showed that surface roughness is highly influenced by feed rate, with lower rates resulting in finer finishes. Cutting speed had very little effect, whereas the depth of cut demonstrated a considerable influence. The best values for the machining parameters were found to be 27 rpm, 0.023 feed rate, and 0.05 depth of cut which is going to combination of parameter 3. The findings show that feed rate during HAp milling has the greatest effect on surface roughness, with lower rates producing better finishes. The optimum combination of cutting speed, feed rate, and depth of cut for a perfect surface finish is successfully determined by the study.